Tajik-Wakhi language contact - Jaroslava Obrtelová (Orientalia Suecana, 2022)
The present study of language contact between the Tajik (West-Iranian) and Wakhi (East-Iranian) languages spoken in Tajikistan has been undertaken from a synchronic perspective. Specific manifestations of the language contact are studied within the context of the current sociolinguistic situation of the endangered minority Wakhi language and in relation to code-switching, diglossia and borrowing. Tajik-Wakhi contact is understood as unidirectional; i.e., Wakhi is influenced by the majority and official Tajik language, but Tajik is not influenced in return. The study focuses on describing the contact-induced phenomena occurring on the level of morphosyntax, clause-combining and discourse. The phenomena addressed in the article are the use of the ezafe linking particle -i, the use of the Tajik plural endings -o/-on, the adversative conjunction am(m)o, the use of the borrowed subordinator ki, co-occurrence of the borrowed ki and agar with the native subordinator cǝ, and finally, interference of the Tajik verb system with the native Wakhi verb system in narration.